2023
DOI: 10.3390/ma16134824
|View full text |Cite
|
Sign up to set email alerts
|

Zn-Doped Calcium Magnesium Phosphate Bone Cement Based on Struvite and Its Antibacterial Properties

Abstract: The development of magnesium calcium phosphate bone cements (MCPCs) has garnered substantial attention. MCPCs are bioactive and biodegradable and have appropriate mechanical and antimicrobial properties for use in reconstructive surgery. In this study, the cement powders based on a (Ca + Mg)/P = 2 system doped with Zn2+ at 0.5 and 1.0 wt.% were obtained and investigated. After mixing with a cement liquid, the structural and phase composition, morphology, chemical structure, setting time, compressive strength, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Mg has been co-doped with other trace elements such as silver and zinc. A recent study has shown that the incorporation of silver in magnesium-doped biphasic calcium phosphate nanoparticles results in excellent cytocompatibility with human bone marrow-derived mesenchymal stem cells, and demonstrates antibacterial properties against E.coli and S. aureus bacteria [26,27]. Due to the importance of the Mg presence and concentration and the incorporation method, Mg was added to BrC and the physical and mechanical properties of the cement were evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Mg has been co-doped with other trace elements such as silver and zinc. A recent study has shown that the incorporation of silver in magnesium-doped biphasic calcium phosphate nanoparticles results in excellent cytocompatibility with human bone marrow-derived mesenchymal stem cells, and demonstrates antibacterial properties against E.coli and S. aureus bacteria [26,27]. Due to the importance of the Mg presence and concentration and the incorporation method, Mg was added to BrC and the physical and mechanical properties of the cement were evaluated.…”
Section: Discussionmentioning
confidence: 99%